Penggunaan Media Sosial Terhadap Pembentukan Identitas Dan Kesehatan Mental Siswa SMK Negeri 4 Kota Palangka Raya - Mega Kurniawati; Ni Putu Diah Agustin Permanasuri; Adhevia Marissa (FKIP Universitas Palangka Raya, 2026)
This study aims to analyze the relationship between social media use, identity formation, and students’ mental health. The research employed a quantitative approach using a survey method involving 18 respondents. Data were collected through questionnaires and analyzed descriptively and inferentially using Microsoft Excel and SPSS. The findings indicate that most respondents perceive social media as playing a role in the process of identity formation and influencing their psychological condition. However, statistical analysis revealed that the relationship between social media use and the variables studied was weak and not statistically significant (R = 0.167; p > 0.05). These findings suggest that social media use is not a dominant factor in determining students’ identity formation or mental health. Other factors, such as family environment, social interactions, and individual conditions, are also likely to contribute to these aspects. This study provides a preliminary understanding of the complexity of the relationship between social media use and adolescents’ psychological development in the digital era.